Y-1(12-2x)=6

Simple and best practice solution for Y-1(12-2x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-1(12-2x)=6 equation:


Simplifying
Y + -1(12 + -2x) = 6
Y + (12 * -1 + -2x * -1) = 6
Y + (-12 + 2x) = 6

Reorder the terms:
-12 + Y + 2x = 6

Solving
-12 + Y + 2x = 6

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + Y + 12 + 2x = 6 + 12

Reorder the terms:
-12 + 12 + Y + 2x = 6 + 12

Combine like terms: -12 + 12 = 0
0 + Y + 2x = 6 + 12
Y + 2x = 6 + 12

Combine like terms: 6 + 12 = 18
Y + 2x = 18

Add '-2x' to each side of the equation.
Y + 2x + -2x = 18 + -2x

Combine like terms: 2x + -2x = 0
Y + 0 = 18 + -2x
Y = 18 + -2x

Simplifying
Y = 18 + -2x

See similar equations:

| 2x^2+7x-32=0 | | X+15=3x-75 | | 65-2c=-23 | | (30-1y)+1y=30 | | -140/21 | | -6x+10y=134 | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(-10x^2)=0 | | 180+7x=360 | | (20-2x)(10-2x)(x)= | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(10x^2)=0 | | 5c+3=29 | | 2x+2(x+6)=12 | | 3x^2-12x^2+36x=0 | | 4s-8=15 | | 2x^2-36x=720 | | 18+8x=88 | | (25x^2-100x+50)(50x-50)(2x)-(-100x)(5-5x)(10x^2)=0 | | 5/7x3/5 | | 5y-20+110+y=180 | | W-4.40=9.60 | | x=30+-1y | | (9y+3)(3x+10)= | | -6y+10x=134 | | 3(4+1)=8(-2x+3) | | 10sin(c)-cos(c)=8 | | 0=16z^3-z | | 1+3(9-6)-4= | | 2=-1.5(4)+b | | x-5-1=x-11/4 | | 6r=87 | | 2h^3+2h^2t-4ht^2= | | 20-4x+2x= |

Equations solver categories